Systemic disease and the lung. (June 2016) - Chua, Felix; Saunders, Peter
Abstract: Pulmonary manifestations of systemic disease occur in a wide range of conditions, including, most commonly, connective tissue diseases such as scleroderma and rheumatoid arthritis. Certain haematological malignancies are associated with acquired pulmonary alveolar proteinosis. The treatment of myelo-lymphoproliferative diseases with bone marrow transplantation can cause obliterative bronchiolitis as part of a graft-versus-host response. Infectious pathologies such as HIV disease can predispose to opportunistic lung infection, pulmonary lymphoid disorders and cancer. Liver disease occasionally affects the pulmonary circulation, and inflammatory bowel disease the airways. This review will highlight how systemic disease can lead to respiratory manifestations ranging from mild to life-threatening.